Upaya Meningkatkan Pemahaman Membaca Bahasa Inggris melalui Pembelajaran Berbasis Inkuiri (Inquiry-Based Learning - Kholili, Achmad (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
One of the difficulties that are often experienced by students in learning English is reading. Reading is an activity that occurs every day at school, at home, or in public places. Students in Indonesia have difficulty understanding English reading, mainly due to lack of practice, lack of vocabulary they have, and lack of knowledge about strategies for understanding English reading text. This education service is done to address the problems in reading by using training methods. The approach used in this service is inquiry-based learning. The results of this education service can be concluded that students can understand English reading well after they are trained to cope with problems in reading comprehension through an inquiry-based learning approach by collaborating and consulting with the educator. Therefore, the inquiry-based learning approach is very effective to be applied in both formal and non-formal school environments.